2021
DOI: 10.1002/ejoc.202100618
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aerobic Oxidation of N‐Pyridylindole Leading to Fused Quinazolinones

Abstract: Copper catalyzed aerobic oxidation enables the tandem selective and efficient transformation of N‐pyridylindole for the construction of 11H‐pyrido[2,1‐b]quinazolin‐11‐ones. The reaction shows good efficiency to accomplish the aerobic oxidation. Mechanistic investigation indicated the facile oxidation of N‐pyridylindole underwent the single‐electron‐transfer oxidation, the capture of molecular oxygen and the extrusion of carbon monoxide to deliver the desired 11H‐pyrido[2,1‐b]quinazolin‐11‐ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…1 Due to their extensive applications, the functionalization of indoles has long been an attractive topic in synthetic chemistry. 2 Organic compounds containing aryl C–N moieties are ubiquitous in functional materials and natural products. As such, direct C–H amination has emerged as an attractive approach to synthesize these compounds, characterized by several appealing features, such as high atom economy, high step economy and synthetic practicality.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to their extensive applications, the functionalization of indoles has long been an attractive topic in synthetic chemistry. 2 Organic compounds containing aryl C–N moieties are ubiquitous in functional materials and natural products. As such, direct C–H amination has emerged as an attractive approach to synthesize these compounds, characterized by several appealing features, such as high atom economy, high step economy and synthetic practicality.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the electron-withdrawing group (CF 3 ) could still afford the corresponding product 34e in 50% yield. 26 The reaction was performed with 20 mol% of Cu(OAc) 2 , 30 mol% of imidazole 36 as a ligand, and 1.0 equiv. of PivOH in DMSO.…”
Section: Ring-opening Strategy Of Indoles To Prepare 23-fused Quinazo...mentioning
confidence: 99%
“…In 2020, Liu et al reported the copper-catalyzed aerobic oxidation of N -pyridylindole 35 to synthesize pyrido[2,3- b ]quinazolinones 37 in good yields (Scheme 18). 26 The reaction was performed with 20 mol% of Cu(OAc) 2 , 30 mol% of imidazole 36 as a ligand, and 1.0 equiv. of PivOH in DMSO.…”
Section: Ring-opening Strategy To Prepare 23-fused Quinazolinonesmentioning
confidence: 99%
“…Consequently, remarkable efforts have been devoted to their efficient synthesis in the past few years [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Traditionally, 2,3-fused quinazolin-4(3 H )-ones can be prepared through multiple pathways, such as dehydrogenative cross-coupling reactions [ 16 , 17 , 18 , 19 , 20 , 21 ], oxidative ring-opening reactions [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], cycloaddition reactions [ 29 , 30 , 31 , 32 ], etc. However, these methods suffer from the use of complicated starting materials, harsh reaction conditions, and complex reaction procedures.…”
Section: Introductionmentioning
confidence: 99%